Molecular Surveillance of Dengue Virus Serotype Using Polymerase Chain Reaction in Surabaya 2013 - Sucipto, Teguh Hari; Labiqah, Amaliah; Churrotin, Siti; Ahwanah, Nur; Mulyatno, Kris Cahyo; Soegijanto, Soegeng; Kotaki, Tomohiro; Kameoka, Masanori; Konishi, Eiji (Indonesian Journal of Tropical and Infectious Disease, 2014)
Dengue is one of the infectious diseases which is endemic in the tropical and sub-tropical country. The disease found in Indonesia Surabaya, 1968. The symptoms of Dengue virus infections are two kinds, first DF (Dengue Fever), second DHF (Dengue Hemorrhagic Fever). This infectious disease transmitted by Aedes aegypti mosquito. Mosquitoes breed in clean water areas. More than 100,000 cases of DF/DHF ccurred in Indonesia every year. The purpose of this study were to provide information and the spread of dengue virus types in Surabaya from January 2013 to September 2013. The nalysis technique used to determine the type of dengue virus nfectionwas used PCR (Polymerase Chain Reaction). The results obtained 69% DENV-1, 27% DENV-2 isolates, 4% isolates DENV-3, and 0% DENV-4 isolates.